Fostering Institutions to Contain Corruption - World Bank (Washington, DC, 2012)
Corruption is bad for development. Leaving aside the morality of bribe taking, influence peddling, embezzlement, and other abuses of power for personal or narrow group gain, corruption impedes investment and growth and exacerbates poverty and inequality. Human beings are prone to self-seeking behavior. What constrains individual behavior and makes it conform to larger collective ends includes the laws that form the core of norms and institutions. Corruption can never be completely or permanently eliminated. Effective and durable corruption control requires multiple, reinforcing, and overlapping institutions of accountability. And where corruption is endemic, these institutions need to be of three kinds: horizontal accountability, vertical accountability, and external accountability.